The Existence of Personal Values in the Adventure of Dinoko and Dinoki 2022 by Imron W Haris: Child Literary Work Review - ALFADLILAH, MUNA; Maftukhan, Muhammad (Hasta Wiyata, 2024)
Children understand and respond psychologically to child literary work. In 2022, the researcher scrutinized Imron W. Harits' children's storybook, The Adventure of Dinoko and Dinoki. This English-language storybook has intriguing intrinsic and extrinsic elements, complemented by illustrations of the characters Dinoko and Dinoki. The researcher examines the personal values of each character in this book, which has seven subheadings. The researcher employs a descriptive qualitative research method, utilizing data collection techniques of reading and noting. This process entails reading and observing each subheading, noting the data, classifying the data, and finally entering the data into a data table to streamline data analysis. The research results depict personal values, such as emotions, struggles, friendships, or social and intellectual feelings, thereby serving as a reflection of education for children